Differentially expressed circular RNAs and their diagnostic value in children with allergic rhinitis - Yuhao Fan; Yilin Li; Miaomiao Xu; Liya Ren; Yong Li; Jing Li (Journal of International Medical Research)
Background We aimed to elucidate the pathogenesis of allergic rhinitis by analyzing aberrantly expressed circular RNAs and exploring their diagnostic value. Methods Blood samples were collected from allergic rhinitis patients and healthy controls, and circular RNA microarray was performed. The expression of differentially expressed circular RNAs was verified via real-time quantitative reverse transcription polymerase chain reaction, and these RNAs were selected for Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses. Spearman’s correlation analysis was used to evaluate the relationship between hsa_circRNA_0008999, hsa_circRNA_0059181, disease symptoms, and total serum immunoglobulin E levels. Results Our microarray results revealed the presence of 200 differentially expressed circular RNAs. Two differentially expressed circular RNAs (hsa_circRNA_0008999 and hsa_circRNA_0059181) were selected and verified via real-time quantitative reverse transcription polymerase chain reaction. Gene Ontology analysis showed that hsa_circRNA_0008999 and hsa_circRNA_0059181 were closely related to the positive regulation of ligase activity, proteasome regulatory particle, nicotinamide adenine dinucleotide phosphate binding, and nuclear factor kappa-B–inducing kinase/nuclear factor kappa-B signaling. Kyoto Encyclopedia of Genes and Genomes analysis revealed the enrichment of proteasome, spinocerebellar ataxia, and nucleotide-binding oligomerization domain-like receptor signaling pathway. The circular RNA–microRNA–mRNA regulatory network suggested that hsa_circRNA_0008999 and hsa_circRNA_0059181 regulate the function and expression of microRNAs and mRNAs. The expression of hsa_circRNA_0059181 was correlated with the total symptom score and total serum immunoglobulin E levels in patients with allergic rhinitis. Conclusion We provided valuable information regarding the expression of hsa_circRNA_0059181, which may serve as a biomarker of allergic rhinitis.